“Let the Algorithm Do the Work”: Reduction of Hypoglycemia Using Sensor-Augmented Pump Therapy with Predictive Insulin Suspension (SmartGuard) in Pediatric Type 1 Diabetes Patients - Biester, Torben (Diabetes Technol Ther, 2017)
Background: A sensor-augmented insulin pump (SAP) using the MiniMed(®) 640G system with SmartGuard™ technology allows an automatic stop of insulin delivery based on prediction of low glucose levels. Since pediatric patients are particularly prone to hypoglycemia, this device may offer additional protection beyond conventional sensor-augmented therapy. Methods: This prospective, pediatric multicenter user evaluation assessed 6 weeks of SAP with SmartGuard (threshold setting for hypoglycemia: 70 mg/dL) compared to a preceding period of 2 weeks with SAP only. The primary outcome was the potential reduction in the frequency of hypoglycemic episodes and hypoglycemic intensity (area under the curve [AUC] and time <70 mg/dL). Results: The study included 24 patients with at least 3 months of insulin pump use (average age: 11.6 ± 5.1 years, 15 female, average type 1 diabetes duration: 7.5 ± 4.2 years, mean ± SD) who had on average 3.2 ± 1.0 predictive suspensions/patient/day. The mean sensor glucose minimum during suspension was 78 ± 6 mg/dL and the average suspension time was 155 ± 47 min/day. Use of SmartGuard in patients treated as per the protocol (n = 18) reduced the number of instances in which the glucose level was <70 mg/dL (1.02 ± 0.52 to 0.72 ± 0.36; P = 0.027), as well as AUC <70 mg/dL (0.76 ± 0.73 to 0.38 ± 0.24; P = 0.027) and the time/day the level fell below 70 mg/dL (73 ± 56 to 31 ± 22 min). The reduction of hypoglycemia was not associated with a significant change in mean glucose concentration (171 ± 26 to 180 ± 19 mg/dL, P = 0.111) and HbA1c (7.5% ± 0.5% to 7.6% ± 0.7%, (P = 0.329). Manual resumption of insulin delivery followed by carbohydrate intake resulted in significantly higher glucose levels 1 h after suspension compared to SmartGuard suspensions with automatic resume (190.8 ± 26.5 vs. 138.7 ± 10.3 mg/dL; P < 0.001). Conclusions: SmartGuard technology significantly reduced the risk for hypoglycemia in pediatric type 1 diabetes patients without increasing HbA1c. Patients must be educated that when using combining predictive low-glucose insulin suspension technology, extra carbohydrate intake in response to an alarm combined with manual resumption is likely to cause rebound hyperglycemia. The best results were achieved when the user did not interfere with pump operation.